Innovations in Teaching Strategic Management - PILLANIA, Rajesh K. (Journal of Research in Educational Sciences; Vol 15 No 1 (2024): JRES, Volume XV, Issue 1(17), Summer 2024DO - 10.14505/jres.v15.1(17).04, 2024)
Strategy is a very important but complex discipline. Innovation is necessary for effective teaching of strategy and strategy management. Innovations in teaching strategy and strategic management must focus on four important areas: the teaching goal, the teaching approach, the teaching content, and the learning outcomes. Continuous innovation in teaching strategy and strategic management is necessary to add value to the participants and, through them, to the organizations they work for. When participants and the organizations for which they work realize value by learning strategy and strategic management, it will help achieve the purpose of strategy and strategic management, which is to add value and make an impact. This paper has implications for the practice of strategy and strategic management in industry and academia. The work has limitations as it is based on the experiences of one academic, but that creates the scope for future research. More researchers, practitioners, and academicians can conduct more experiments to establish the suggested innovations further.